Social Engagement as an Initial Capital for the Development of Civic Engagement Students in Boarding Schools - Ikrimah Saputra; Moch. Muchtarom; Triyanto Triyanto (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2020)
Civic engagement is defined as the active participation of citizens individually or collectively in community life based on skills, expertise, knowledge, which combines with values, motivation and commitment to make changes in order to improve the quality of people's lives for the better. The progress of information technology and the very rapid development of science in the current era of globalization, have a negative impact on social change in society. Today's young generation tends to be individualistic and hedonistic. They focus life orientation more on self-achievement rather than being involved in social problems in society. Boarding schools are a suitable environment in an effort to develop civic engagement, especially among boarding students because they have a good social attachment to one another. This study aims to find out how social engagement of students in boarding schools is an important initial capital for the development of civic engagement. This research uses a qualitative method using purposive sampling technique. The subjects of this study include Civics Education teachers, Boarding Advisors, and students. Data collection was carried out using document study techniques, interviews, and observations. Data analysis technique is done by data reduction, data presentation, drawing conclusions, and verification. The results of this study indicate that social engagement among boarding students is influenced by factors of fate, equality of interest, and the presence of intense and continuing interactions. This social attachment is the initial capital for the development of civic engagement, especially in the stages of growing empathy.